Adverse events associated with the rhinomodelation technique with hyaluronic acid in orofacial harmonization (Research, Society and Development, 2023)
Rhinomodelation is a minimally invasive aesthetic procedure performed on an outpatient basis, which seeks to improve the appearance of the nose without the need for plastic surgery. Among the techniques used, the most common is the application of medium reticulation hyaluronic acid. The benefits of this type of rhinomodelation include the absence of prolonged rest, quick return to normal activities, absence of incisions, acceptable dressing, simple post-procedure care and the possibility of total or partial reversal through hyaluronidase injections. However, the inappropriate use of hyaluronic acid can lead to serious complications, such as nasal tissue necrosis, blindness or death. It is essential that the professional who performs the procedure has the necessary knowledge and experience to avoid such complications and improve the patient's quality of life. Thus, the objective of this work is, through a narrative literature review, to demonstrate what are the adverse effects associated with the rhinomodelation technique and how these can be avoided and treated by the dental surgeon, especially by the specialist in orofacial harmonization.